油脂加氢脱氧制备第二代生物柴油催化剂研究进展Research progress on catalysts for hydrodeoxygenation of oils to produce second generation biodiesel - 程瑾，李澜鹏，王兆程，王宜迪，曹长海 CHENG Jin, LI Lanpeng, WANG Zhaocheng, WANG Yidi, CAO Changhai (Zhongguo youzhi, 2024)
第二代生物柴油作为一种重要的石化柴油替代燃料，具有较好的应用前景，催化剂是制约其发展的重要因素。综述了油脂加氢脱氧催化剂的研究新进展，重点论述了油脂加氢脱氧制备第二代生物柴油的反应机制以及催化剂的活性组分、助剂、载体等，分析了催化剂失活的原因，并指出了今后的发展方向。贵金属基催化剂价格昂贵，导致生物柴油生产工艺的成本高，限制了其大规模的工业化生产和技术发展；过渡金属基催化剂价格便宜，但存在催化效果较差、催化剂容易失活等问题；助剂和载体也极大地影响催化剂的活性、选择性和稳定性。综上，对非贵金属基催化剂改性、添加助剂或采用改性复合载体，开发新型、高效、稳定性好的油脂加氢脱氧催化剂是今后的发展方向。As important alternative fuel of petrochemical diesel, the second generation biodiesel has a good application prospect, and the catalyst is an important factor restricting its development. The new research progress on catalysts for oil hydrodeoxygenation was reviewed, including the mechanism of hydrodeoxygenation reaction, the active components, promoters and supporters of the catalyst. The reason of catalyst deactivation was analyzed. Further,the development direction in the future was pointed out. The expensive price of precious metal catalysts leads to high costs in the production process of biodiesel, which limits its large-scale industrial production and technological development. Transition metal catalysts are cheap, but they have issues such as poor catalytic performance and easy deactivation. Promoters and supporters also greatly affect the activity, selectivity, and stability of catalysts. In summary, developing new, efficient, and stable oil hydrodeoxygenation catalysts by modifying non precious metal catalysts, adding promoters, or using modified composite supporters, is the future development direction.